Chapter Cittadinanza e diritti fra 'particolarismo' e 'universalismo': un campo di tensione della modernità - Costa, Pietro (Studi e saggi, 2023)
Starting from eighteenth-century natural law theories and the revolutions of the late eight-eenth century, an essential tension emerged: the tension between rights as an effect of the be-longing of subjects to a specific political community and rights as the patrimony of the human being as such. This tension emerges in full light in constitutional democracies, in the European legal space and in the international order in the second half of the twentieth century and is still waiting to be resolved.